BEBERAPA FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kadirisman, Indra (PRIMA EKONOMIKA, 2018)
The research is purposed to observe the influence of Dividend Per Share(DPS), Earning Per Share (EPS), Return On Investment (ROI), and Net ProfitMargin (NPM) to Share Price (SP) of the listed companies in Indonesian StockExchange.The research is a causality research which observes what and how so far theinfluence of DPS, EPS, ROI, and NPM to SP of the listed companies in IndonesianStock Exchange. Field research is direct field approaching to obtain primary datafrom some available resources in correlation to the research. Classical assumptiontests are treated to test the prerequisite analysis for hypothesis exam of linearregression model, it consists of normality-test, multi-colinearity-test,heteroscedastisity-test, and autocorrelation-test of the research data.The research results show that DPS gives a positive and significant influenceto SP with counted t = 11.552 > t-table and p = 0.000 < 0.05), it implicates that agood DPS (liquidity) will give then a potential profit for HS increasing; EPS givesa positive and significant influence to SP with counted t = 13.800 > t-table and p =0.000 < 0.05, it implicates that sales growing will increase company profit and SP;ROI gives a positive and insignificant influence to SP with counted t = 1.810 < t-table and p = 0.073 > 0.0, it implicates that the company hasn’t good performanceto get good profit and attract investors permanently investee and small increasingof SP; NPM gives a positive and insignificant influence to SP with counted t 0.826< t-table and p = 0.411 > 0.05, it implicates that a great NPM doesn’t givecontribution yet to company and investor getting optimal SP. DPS, EPS, ROI, andNPM give a positive and significant influence to SP with counted F = 96.566 and p= 0.000 < 0.05. However, the Adjusted R2 value is 0.758; it means that the fourindependent variables can describe the change of independent variable SP in orderof 75.8%, whereas the rest 24.2% is described by other factors excluding proposedfour independent variables in this research.